Analysis In The Application Of Plastic Waste As A Constructive Material In Flexible Pavement (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Road construction is the main sign of the development of any country. Day to day increase in the usage of roads leads to frequent deterioration. It causes timely maintenance of roads and sometimes reconstruction also. As the construction cost of the roads is high, one should take pre measures to lessen the maintenance cost. A project is successful not only when it is executed economically but also when the maintenance cost is low. Any material can be given more strength by adding some additives regarding its nature and structure, likewise in roads. Safeguarding of pavements requires a precise approach for the execution of sustainable roads. Due to the increased axel load and speed of the vehicles the ability of bituminous layers is been lessened resulting in seepage, rutting, pot holes. On other hand, day to day increase of various types of wastes that are non-bio- degradable are increasing drastically which in turn are a threat to life. One such type of waste is plastic which is highly impossible to get decomposed in the earth surface. Both these problems can be solved by providing a solution involving by using plastic waste in flexible pavement construction.